Experimental spinal cord injury and behavioral tests in laboratory rats. Issue 3 (March 2019) - Ahmed, Rakib Uddin; Alam, Monzurul; Zheng, Yong-Ping
Abstract: Traumatic spinal cord injury (SCI) results in some serious neurophysiological consequences that alter healthy body functions and devastate the quality of living of individuals. To find a cure for SCI, researchers around the world are working on different neurorepair and neurorehabilitation modalities. To test a new treatment for SCI as well as to understand the mechanism of recovery, animal models are being widely used. Among them, SCI rat models are arguably the most prominent. Furthermore, it is important to select a suitable behavioral test to evaluate both the motor and sensory recovery following any therapeutic intervention. In this paper, we review the rat models of spinal injury and commonly used behavioral tests to serve as a useful guideline for neuroscientists in the field of SCI research.